Paternal parenting behaviour and psychological well-being in Malaysian adolescents: Variation by sex - Yahya, Amira Najiha (2014)
Few studies have focused on the influence of paternal parenting on adolescents’ psychological well-being. Thus, using structural equation modelling, the study sought to elaborate on and clarify the link between paternal parenting behaviour and psychological well-being of adolescents.In addition, the study examined if the relationship vary across sex.A total of 1000 adolescents (mean age: 13.91 year) from government’s daily secondary schools in selected states in Malaysia was sampled using the probability proportional to size (PPS) cluster sampling technique. Paternal parenting behaviour was measured using Malaysian Parenting Behaviour Inventory (Baharudin et al., 2012).Psychological wellbeing was indicated using two measures: General Health Questionnaire (Goldberg, 1978) and Rosenberg’s Self-Esteem Scale (Rosenberg, 1965). Data were obtained through selfadministered questionnaire at the selected schools. Results indicated that paternal warmth, indigenous and harsh discipline had significant influences on adolescents’ self-esteem.However, only paternal harsh discipline had direct relationship to adolescents’ psychological health.A multigroup analysis revealed that the structural relationship between paternal parenting behaviour and adolescents’ psychological well-being is unstable across sex.The study concludes that warmth and indigenous paternal parenting promote adolescents’ self-esteem whereas harsh discipline parenting appeared to suppress self-esteem.Additionally, results revealed that paternal harsh discipline reduced adolescents’ psychological health. Sex of adolescents was further found to interact with the paternal parenting behaviour and adolescent psychological well-being linkage. Findings therefore refined knowledge on the important role of paternal behaviour in adolescents’ development particularly, psychological well-being and its variation by sex.